Potential Investigation on Multiphase Flow of Loaded Dispersion for the Production of Metallized Paper: Investigation on Multiphase Flow of Loaded Dispersion - Suri, Saadat Ullah Khan; Siddique, Mohammad (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The current review research's main objective is to develop dispersion models in the multilayer curtain coating with the production of metallized paper. To achieve this, the curtain coating on the paper substrate is employed with respect to multilayer coating of polymers. The first layer of polymer is applied to the paper and then it is subjected to vacuum metallization with aluminum deposition. After it, another second layer of polymer is subjected on it to prevent it from oxidation. These coated polymers are different in nature. The metallized paper will be produced which has high strength will be formulated in this application of curtain coating. The instability of curtain and air entrainment will be minimized from high Weber number, low Reynolds number, Optimum web speed and Coat weights. The above demonstrated process simulation will be modelled in Ansys-CFD. The dispersion of solids in the curtain flow through substrate moving on the web will be evaluated from different numerical methods. Each method has its own characteristics to study the nature of solids dispersion. The high loaded solids dispersion will be investigated from numerical methods including Langrangian Point Particle, Coarse grained molecular dynamics, Stokesian Dynamics, Brownian Dynamics, Point Particle Method Reynolds Averaged Navier Stokes equation, Eulerian Method, Langrangian-Eulerian Point Particle, Large Eddy Simulation point particle, Combined discrete element and Large Eddy Simulation and Discrete Element Methods.